The Effect of Service Quality on BPJS Patient Satisfaction in the Outpatient Installation at RSU Sinar Husni Medan - Nurmaya Sari; Deli Theo; Mayang Sari (Journal of Health Management, Administration and Public Health Policies, 2025)
The National Health Insurance (JKN) is a government and community program aimed at providing comprehensive health coverage for the Indonesian population, enabling citizens to live healthy, productive, and prosperous lives. Health insurance is closely related to service quality, which directly affects patient satisfaction. This study employed a quantitative design using an analytical survey with a cross-sectional approach. The population consisted of outpatient patients at Sinar Husni General Hospital, Medan, totaling 7,477 individuals, with a sample of 99 selected using accidental sampling. Based on the chi-square test, the relationship between tangible, reliability, responsiveness, assurance, and empathy with BPJS patient satisfaction yielded p-values of 0.002, 0.002, 0.001, 0.001, and <0.001 respectively. There is a significant effect of service quality (tangible, reliability, responsiveness, assurance, empathy) on BPJS patient satisfaction in the outpatient installation.